Sanksi Pidana Denda Dan Manfaatnya Bagi Pelaku Tindak Pidana Pelanggaran Menurut Buku III KUHP - Risma Wanti; Imam Verdinand; Annisa Dwi Salimah; Saryanto; M.Rafi Akbar (Consensus : Jurnal Ilmu Hukum, 2024)
New sanctions for liquidation if other sanctions can't solve the problem. According to article 503 of the Code, interference in the vicinity of a building for the conduct of authorized worship or interruption in the proximity of the building for conducting authorized service is punishable by imprisonment for a maximum of three days or a maximum fine of two hundred twenty-five rupees. According to Book III of the Covenant, the profits obtained by the perpetrator of a criminal offence are as follows: penal sanctions fine preserving the good name or honour of perpetrators of the offence and does not create a bad impression on the person concerned; penal sanction fine prevents bad influence and prevents stumbling.